Digital Tarot: Strategi Membangun Interpersonal Trust melalui Komunikasi Siber - Gabriella Salim (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The rapid development of the modern world has made tarot increasingly recognized by many people. However, the growth of tarot consultation has also generated significant pros and cons within society. Some people believe that tarot consultation is closely related to magical or mystical practices, while others consider tarot cards as a medium used to help individuals find solutions to their problems, both internal and external. In general, tarot consultation involves two individuals engaging in interpersonal communication. Interpersonal communication refers to communication between individuals, occurring when at least two people with different characteristics, values, perspectives, thoughts, and behaviors interact with one another. This study aims to explore the questions arising in society regarding trust in tarot consultations conducted through online chatting, from the perspectives of Pembaca Tarots and clients. Therefore, this research focuses on interpersonal communication strategies used by Pembaca Tarots to build trust with clients through online chatting. The objective of this study is to identify these interpersonal communication strategies in fostering client trust. This research employs a descriptive qualitative method, presenting detailed descriptions of communication strategies and processes. Data were collected through in-depth interviews, observation, documentation, and literature review. The results show that each Pembaca Tarot has unique strategies in building client trust through online chatting. In general, these strategies involve establishing a good relationship with clients by providing excellent service.